A randomized controlled twelve month clinical study on the evaluation of success rate of endodontically treated teeth restored with metal poly-fiber posts and dentin posts - Sarvesh Shrikantbhai Patel; Rajesh Sethuraman (Wolters Kluwer Medknow Publications, 2022)
Settings and Design: Department of Prosthodontics, KMSDCH, SVDU, Randomised Controlled study. Materials and Methods: Thirty-six teeth that satisfied selection criteria were randomly allocated and treated in the two intervention groups - metal fiber post with composite core and dentin post with composite core. Patient characteristics with respect to gender, tooth guidance, type of tooth, and mobility amount of tooth structure left were recorded. The primary outcome of tooth loss and the secondary outcomes of recurrent caries detected at the crown margin, de-cementation of crown, and fracture of the core, post, and root were recorded at baseline, 3, 6, and 12 month follow up. Statistical Analysis Used: Chi Square test. Results: Thirty-six teeth in 17 patients (10 males and 7 females) were treated using metal fiber post (18 teeth) and dentin post (18 teeth). No loss of tooth was seen at the end of 3, 6, and 12 months. The secondary outcomes also showed no recurrent caries at margin and no fracture of core, post, and root in both the groups at the end of 3, 6, and 12 months. One case of de-cementation was observed in both the groups at the 12-month period. Periodontal and periapical conditions showed no clinical and radiographic signs at any of the follow-up periods in both the groups. Conclusion: This twelve month randomized controlled clinical study concluded a similar success rate for endodontically treated teeth restored with crowns on both metal fiber post with composite core and dentin post with composite core.